Ichthyotoxicity of selected Philippine soft coral species. - Jacobo, Celbert B.
Toxins from three species of Philippine soft corals from Piagao island (part of the Taklong National Marine Reserve) in Guimaras were each extracted with water. The extracts were tested for fish toxicant activity on tilapia (Oreochromis ssp.) fry in a 48-hour bioassay . All three species showed ichthyotoxicity with 48-hour LC 50 at 0.50 ppt for Sinularia sp., at 0.86 ppt for Sarcophyton sp., and at 1.34 ppt for Lithophyton sp..